A COMPARATIVE STUDY OF SISTERS’ LEADERSHIP STYLES AND THEIR JOB SATISFACTION IN ZETAMAN SISTERS OF THE LITTLE FLOWER CONGREGATION AT TAUNGGYI ARCHDIOCESE, SHAN STATE, MYANMAR - Lwin, Mary Wai Wai; Ye, Yan (Scholar: Human Sciences, 2015)
The purposes of this study were: 1) to compare the Sisters’ Leadership styles in Zetaman Sisters of the Little Flower Congregation; 2) to determine the Sisters’ Job Satisfaction levels in Zetaman Sisters of the Little Flower Congregation, and 3) to compare the Sisters’ Job Satisfaction among different Leadership Styles in Zetaman Sisters of the Little Flower. This research was conducted in Zetaman Sisters of the Little Flower Congregation, Taunggyi Archdiocese, Myanmar. All 80 sisters in the congregation were distributed the surveys and all surveys were returned. The research was designed as a survey research. The researcher identified sisters’ leadership styles, including autocratic leadership style, democratic leadership style and laissez-faire leadership style. Extrinsic job satisfaction, intrinsic job satisfaction and overall job satisfaction were used to determine the sister’s job satisfaction in this study. The collected data were analyzed by frequency, percentage, mean, standard deviation, and one-way ANOVA. The study found out that most of the sisters in congregation had practiced democratic leadership styles. The sisters’ job satisfaction was at “Satisfied” level, which meant they were satisfied with their jobs in the Congregation, Myanmar. However, the research found there was no significant difference of sisters’ job satisfaction among different leadership styles in the Congregation. Recommendation for the sisters to strengthen their leadership styles and job satisfaction by providing self-learning, peer learning, group learning to learn and share, to ensure different personal growth and to practice appropriate leadership styles which leads to the ultimate success in developing sisters in both their leadership styles and congregation.